Pendampingan dan Penyuluhan Siswa-Siswi SMA Katolik ST. Bonaventura Madiun dalam Menentukan Pilihan untuk Kuliah, Bekerja atau Bekerja Sambil Kuliah Setelah Lulus Sekolah - Hartirini Warnaningtyas; Djuwitawati Ratnaningtyas; Mintarti Indartini (Universitas Merdeka Madiun, 2024)
The purpose of this community service is helping provide direction to St. Bonaventura in choosing his goals after graduating from school, opening the paradigm for St. Bonaventura towards a bright future, and providing enthusiasm and motivation for St. Bonaventura in living life after graduating from school. The methods used in this community service are expository, namely conveying material verbally and inquiry, namely learning that emphasizes critical and analytical thinking processes related to human resource management skills and marketing management with in-depth understanding of the material on how to determine the future.The results of counseling and outreach carried out to grade 11 students of St. Catholic High School. Bonaventura's 42 students are 41 of them chose to continue their education/college and one person worked to continue his parents' business